Analysis of actinometric measurements under all-sky and cloud-free conditions in Cáceres (Spain) for the period 1913–1920. Issue 1 (1st January 2019) - Bravo-Paredes, Nieves; Gallego, María Cruz; AntÓn, Manuel; NÚÑEz, Marcelino; Vaquero, JosÉ Manuel
Abstract: Early daily actinometric and cloud cover data from Cáceres (SW of Spain) were recovered for the period 1913–1920. The task of retrieving and digitising early actinometric data series turn out highly required due to the lack of solar radiation data throughout the first half of twentieth century. Firstly, the Arago actinometer and the procedure employed to record the actinometric data were described in detail. Additionally, in spite of being a short series, trends from recovered actinometric data were analysed. A negative trend of (−0.16 ± 0.03) °C/year was obtained for all-sky conditions, reaching a marked value of (−0.26 ± 0.04) °C/year when cloud-free days were selected in the analysis. Both trends were statistically significant at the 95% confidence level. The Katmai eruption in June 1912 likely caused anomalous low actinometric records in 1913 and 1914. These results suggest a decrease of solar radiation in Cáceres during the second decade of the twentieth century which is in accordance with the final stage of the long-term negative trend in solar radiation data observed at several European sites from late nineteenth century to the beginning of the twentieth century ('early dimming').